The research and teaching of Ilocos history - Apilado, Digna Balangue (2006)
The inclusion of local history studies in the academic program of high schools, colleges, and universities is in accordance with the goal of a more nationalistic education for Filipinos. Local history studies would contribute to the generation of knowledge, promote appreciation of the history and culture of a region or province, and enhance the process of economic and political development. There is at present a substantial amount of studies already done on the Ilocos, but there still remain many gaps in data on certain periods and aspects, and how we hope to understand the region?s history. This paper will deal with these two aspects that are, basically, how to do research and how to teach. The paper will mention some published sources on Ilocos history and researches of local scholars. A survey of these sources will show the areas of research that have been done and what still needs to be done. This general survey will then be followed by some strategies for teaching, such as subjects to be instituted in a curriculum, topics that can be discussed in history courses, and establishing a resource center for historical and cultural research.
Includes bibliographical references (pages 303-305).